G20's contribution to inclusive and resilient global value chains while promoting involvement of least developed countries - Neha Gupta (Asian Development Bank Institute (ADBI), 2024)
This paper uses export and import shares of intermediate goods to assess the extent of integration of G20 and non-G20 nations, including least developed countries (LDCs), in global value chains (GVCs). The G20's intermediate trade, especially the imports, recovered fast during and immediately post-pandemic, exhibiting many members' inherent capacity to adjust to shocks. The G20's developed countries, mainly G7 and other EU nations, are found to have greater supply chain resilience (SCR) scores. However, a wide gap continues to exist between G20 developed nations' demand for inputs and G20 developing nations' supply of inputs, despite rising exports for many developing countries. This implicitly points to lower south-south cooperation, i.e., the limited intermediate trade among G20 developing nations and of this subgroup with LDCs. The share of non-G20 nations, covering several countries from the south, has also declined in global intermediate trade post-pandemic. Nevertheless, this group, mainly ASEAN, has a decent presence in intermediate exports. The primary issue is the incessantly low involvement of LDCs in intermediate trade, reaching just around 1% in GVCs. G20-developing nations' imports from LDCs are marginally growing with shares in the range of 2%-3%, compared to shares below 1% in the case of linkages with the G20-developed nations' supply chains. This implies slower and limited fulfillment of the G20's long-standing commitment to creating inclusive GVCs. It is found that LDCs' infrastructure quality and FDI inflows have been very low with continually lower supply chain visibility, presenting many of them as least resilient countries. This paper affirms that creating resilient GVCs needs a holistic long-term solution where no country, especially low-income ones, is left behind (inclusiveness). Domestic reforms in the G20's developing countries will play an influential role. These reforms can stimulate LDCs to learn and adopt best practices. The paper suggests vigilant identification of barriers to the integration of LDCs. This is to be followed by more capacity building and resilient improvement programs, sharing of information on markets and regulations, and regular training programs by the G20 in collaboration with multilateral agencies on labor and environmental standards. It is a prerequisite for upgrading in GVCs especially to link with the lead firms mostly located in the developed countries. More aid and technical assistance from the G20 are required for LDCs to build regional connectivity, support their MSMEs, expand exports, and build the required digital infrastructure. South-south trade enhancement will help to deeply connect G20-developing nations, ASEAN, and LDCs. The G20 can act as an active discussion forum for GVCs, regularly bringing all the leaders together to discuss challenges and devise knowledge databases for joint solutions.
Keywords: F13; F15; F40; O50; 330; global value chains; G20 and trade; LDCs; inclusive GVCs; supply chain resilience